2020
DOI: 10.14295/bds.2020.v23i4.2060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CAD/CAM Material and Preparation Design on the Long-term Fracture Resistance of Endocrowns Restoring Maxillary Premolars

Abstract: Objective: To evaluate the effect of different occlusal preparation designs and CAD/CAM materials on the fracture resistance of maxillary premolars endcrowns. Materials and Methods: sixty-four endodontically treated upper first premolars were randomly divided into four groups according to ceramic materials (Vita Enamic and IPS emax CAD) and occlusal preparation designs (Anatomical and horizontal butt joint). After teeth preparation, the restorations were all made by CAD/CAM system (Cerec MCXL). Half of each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Central incisors restored with conventional crowns and endocrowns survived thermomechanical loading without loss of retention or fracture [17]. The same dental element in the study by Alghalayini et al [18] demonstrated cracks in both restorations with the number of these failures being high throughout loading.…”
Section: Agingmentioning
confidence: 88%
See 4 more Smart Citations
“…Central incisors restored with conventional crowns and endocrowns survived thermomechanical loading without loss of retention or fracture [17]. The same dental element in the study by Alghalayini et al [18] demonstrated cracks in both restorations with the number of these failures being high throughout loading.…”
Section: Agingmentioning
confidence: 88%
“…The findings of Biacchi and Basting [10] from mechanical strength data, consider Endocrown as a restorative strategy for endodontically treated molars with extensive coronal destruction capable of replacing conventional pin-supported crown. Finally, marginal adaptation research shows similarities between the performance of conventional crowns with long and short pins and Endocrowns for maxillary central incisors [17].…”
Section: Endocrown Versus Conventional Crownmentioning
confidence: 90%
See 3 more Smart Citations